2009
DOI: 10.1111/j.1551-6709.2008.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the Hands to Identify Who Does What to Whom: Gesture and Speech Go Hand‐in‐Hand

Abstract: In order to produce a coherent narrative, speakers must identify the characters in the tale so that listeners can figure out who is doing what to whom. This paper explores whether speakers use gesture, as well as speech, for this purpose. English speakers were shown vignettes of two stories and asked to retell the stories to an experimenter. Their speech and gestures were transcribed and coded for referent identification. A gesture was considered to identify a referent if it was produced in the same location a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 29 publications
10
116
4
2
Order By: Relevance
“…This finding also points to the strength of intonation over visual cues. Additionally, we concluded that SEP participants do not necessarily need more time to react when being exposed to incongruent stimuli, as suggested by previous studies such as Chen (2003), and Schneider et al (2011): Reaction times of SEP participants were shorter when exposed to manipulated stimuli from their native variety, than when exposed to original stimuli.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…This finding also points to the strength of intonation over visual cues. Additionally, we concluded that SEP participants do not necessarily need more time to react when being exposed to incongruent stimuli, as suggested by previous studies such as Chen (2003), and Schneider et al (2011): Reaction times of SEP participants were shorter when exposed to manipulated stimuli from their native variety, than when exposed to original stimuli.…”
Section: Resultssupporting
confidence: 80%
“…As mentioned in Section 2.3, reaction times (RTs) were also measured in order to observe whether participants need more time to react when being exposed to stimuli that are more difficult to categorize (Chen, 2003;Schneider et al, 2011). In this sense, we expect longer reaction times in the VO condition than in the AO and AV conditions for both varieties (Hypothesis 5).…”
Section: Do Participants Need More Time To React To Stimuli More Diffmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, when introducing a new protagonist in a narrative, adult speakers often assign them to a specific area by placing or directing a gesture to the area. When the same referent is mentioned again later, the same location is gesturally indicated (Gullberg, 2006;So, Kita, & Goldin-Meadow, 2009). In other words, once a location is assigned to a particular referent, it is often maintained throughout the discourse, not unlike the use of space for co-reference in sign language (e.g., Bellugi & Klima, 1982).…”
mentioning
confidence: 99%